Raman spectroscopic characterization of novel carbon‐bonded filter compositions for steel melt filtration. (19th December 2013) - Röder, Christian; Weißbach, Torsten; Himcinschi, Cameliu; Kortus, Jens; Dudczig, Steffen; Aneziris, Christos G.
<x xml:space="preserve">Abstract</x> In this work, Raman scattering results on novel carbon‐bonded filter compositions are presented. Such filters are already used for steel melt filtration; however, the potential of this carbon‐bonded Al2O3–C system regarding material characteristics and filtration efficiency has not been fully understood yet. In order to investigate thermally induced structural changes of the filter compositions, micro‐Raman spectroscopy was applied. Analyzing the position, intensity, and full width at half maximum of G and D peaks in the Raman spectra, it could be determined that the carbon appears in graphitic form and the graphitic cluster size was estimated. We found an increase of the lateral cluster size La with increasing coking temperature. Copyright © 2013 John Wiley & Sons, Ltd.